Administrative Challenges in Implementing Renewable Energy Policies in Public Administration and Policy Effectiveness - Wahab, Abdul; Hasrul, Muh.; Syarifuddin, Sandi (Journal Social Civilecial, 2023)
This paper analyses the significance of public administration in the process of renewable energy policies adoption and in the practical problematics around implementation of the strategic goals and detected discrepancies between them. Given the growing global quest for the use of renewable energy sources, the efficient deliverables of renewable energy policies are crucial to addressing environmental, economic, and energy security problems. The current study establishes that there are several administrative challenges that hamper the probability of achieving renewable energy objectives; including lack of resources, political hurdles and weak local capacity. Employing a qualitative research method, the work aims at comparing countries’ overall pledges of renewable energy with the actual practices within local governments to unravel how public administrators manage such disparities. As such, the study is clear on policy relevance: better correspondence of their requirements to domestic capabilities of governance and prediction of potential deficiencies, as well as a constant practice of policy shares with various stakeholders. The work compares the results with global trends and case studies of similar countries/regions and contributes to the evaluation of factors that drive REFs in developing countries with a least administrative power. Based on the findings from this research, the following policy implications are discussed, in terms of their relevance to policymakers: Greater attention should be paid to reinforcing institutional support, increasing the intensity of cooperation between different levels of government, and developing capacities for the effective implementation of renewable energy policies at regional and local level.